Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/clc.4950250707
|View full text |Cite
|
Sign up to set email alerts
|

Coronary collaterals during single‐vessel coronary angioplasty: Effects of nitroglycerin

Abstract: SummaryBackground: Although the protective role of collaterals in coronary artery disease (CAD) is well known, the influence of drugs on collateral function remains controversial.Hypothesis: We aimed to investigate prospectively the prevalence of spontaneously visible and recruitable coronary collaterals in consecutive patients with single-vessel CAD and the effect of systemic administration of nitroglycerin on these types of collaterals during percutaneous transluminal coronary angioplasty (PTCA).Methods: Ips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…[25][26][27][28] In a study of 450 patients, Pohl and colleagues 25 observed that percent diameter stenosis of a coronary artery was the only independent predictor of CFI in the corresponding territory, although the association was relatively weak (rϭ0.10). We have demonstrated an even stronger correlation between CFI and anatomic and functional stenosis severity at the time of PCI that supports the concept that collateral development may be promoted by chronic myocardial ischemia.…”
Section: Determinants Of Collateral Supplymentioning
confidence: 99%
“…[25][26][27][28] In a study of 450 patients, Pohl and colleagues 25 observed that percent diameter stenosis of a coronary artery was the only independent predictor of CFI in the corresponding territory, although the association was relatively weak (rϭ0.10). We have demonstrated an even stronger correlation between CFI and anatomic and functional stenosis severity at the time of PCI that supports the concept that collateral development may be promoted by chronic myocardial ischemia.…”
Section: Determinants Of Collateral Supplymentioning
confidence: 99%
“…Several risk factors associated with PMI after off-pump CABG were reported. The presence of collaterals could protect the patients against PMI [11]. We found that the risk of PMI was associated with increasing the number of distal anastomoses.…”
Section: Discussionmentioning
confidence: 74%
“…Grade 0 means no visible collaterals, grade 1 means collateral filling without epicardial segment visualization, grade 2 means partial epicardial filling, and grade 3 means complete epicardial filling [15]. In some cases, post-MI angiogenesis may help construct collateral flow to the damaged myocardium, or in the case of preexisting collateral flow, increase it [14,16,17]. Thus, in patients whose first MPS revealed nonviable myocardium, a secondary MPS to assess viability may be beneficial and alter the course of treatment strategies, making a revascularization procedure to be necessary [18].…”
Section: Introductionmentioning
confidence: 99%